The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0046184
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 2009 Pandemic A/Beijing/501/2009 H1N1 Influenza Strain in Human Airway Epithelial Cells and Ferrets

Abstract: BackgroundA novel 2009 swine-origin influenza A H1N1 virus (S-OIV H1N1) has been transmitted among humans worldwide. However, the pathogenesis of this virus in human airway epithelial cells and mammals is not well understood.Methodology/Principal FindingIn this study, we showed that a 2009 A (H1N1) influenza virus strain, A/Beijing/501/2009, isolated from a human patient, caused typical influenza-like symptoms including weight loss, fluctuations in body temperature, and pulmonary pathological changes in ferret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The virus strains used in this study included influenza virus A/Beijing/501/2009 (H1N1), an influenza virus isolated from a confirmed H1N1 influenza case in Beijing during 2009 [26,27], and A/Puerto Rico/8/34 (H1N1), a well characterized and mouse-adapted laboratory strain of influenza virus used as the genetic backbone for viruses from which inactivated influenza virus vaccines are generated. The A/Beijing/501/2009 H1N1 virus does not carry the D222G mutation reported in some H1N1 pandemic strains.…”
Section: Methodsmentioning
confidence: 99%
“…The virus strains used in this study included influenza virus A/Beijing/501/2009 (H1N1), an influenza virus isolated from a confirmed H1N1 influenza case in Beijing during 2009 [26,27], and A/Puerto Rico/8/34 (H1N1), a well characterized and mouse-adapted laboratory strain of influenza virus used as the genetic backbone for viruses from which inactivated influenza virus vaccines are generated. The A/Beijing/501/2009 H1N1 virus does not carry the D222G mutation reported in some H1N1 pandemic strains.…”
Section: Methodsmentioning
confidence: 99%
“…Since different studies have reported that H1N1pdm09 can induce apoptosis in late, but not in early stage of viral replication ( Yang et al, 2011 , 2012 ), we assessed the ability of the NS reassortants Gi-NS-PR8 and Gi-NS-Vict to induce late stage apoptosis (10 h p.i.) in A549 cells compared to Gi-wt.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza virus NS1 protein interacts with β-tubulin, which arrests the infected cells in G2/M phase and affects Bcl-2 phosphorylation [290,291]. This, in turn, activates NFk B and induces INF-α and INF-β [292], which then induce the apoptosis cascade by induction of SOCS-3 expression [293,294]. Shiozaki et al, showed the cellular pro-apoptotic protein Siva-1 in A549 cells was involved in IAV replication through caspase activation [295].…”
Section: Referencementioning
confidence: 99%
“…Clusterin, a host protein, attenuates IAV NP-induced apoptosis and IAV replication [296]. Yang et al demonstrated that 2009 pandemic H1N1 A/Beijing/501/2009 could induce caspase-3-dependent apoptosis in the A549 cell line [292]. Husain and Harrod showed that caspase-3-mediated histone deacetylase 6 (HDAC6) cleavage in IAV-infected MDCK cells caused further damage in these cells [297].…”
Section: Referencementioning
confidence: 99%